On the Concepts of Imported Language and Newspeakerism in the Sociolinguistic Context of Lithuania - Likhachiova, Alla (Slavistica Vilnensis, 2020)
This article outlines the advantages of introducing some new terms to describe the current sociolinguistic situation in Lithuania. Its essential components are the heterogeneity of the country’s ethno-linguistic landscape, intensive internal and external migration and the different types of language practices within the country, which are the result of the first two factors. The term “imported language” proposed by the author of the article and the term “newspeakerism”, which has recently become established in European sociolinguistics, have not yet been used in the works of Lithuanian sociolinguists. However, these terms can be important for describing the linguistic specifics of some regions of Lithuania. The first term seems appropriate to denote the language of immigrants, which is used relatively widely in the host country, not only in family, but also in the everyday and official communication, and the second – for the sociolinguistic categorization of such immigrants. Most immigrants are residents of post-Soviet countries with native or well-mastered Russian language, therefore, in the article, it is Russian that is defined as an imported language.The paper examines the theoretical prerequisites for the introduction of new terms for a more accurate description of the current linguistic situation in Lithuania and the designation of its participants. Statistical data on migration processes in Lithuania and fragments of interviews with immigrants of chronologically different arrival streams are used.
Keywords: sociolinguistic situation; migration; immigrants; Russian language; imported language; newspeakers